Fuzzy expert system for drinking water quality index - Mishra, Nidhi; Jha, P (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The role of water in human life is significant as it plays a very essential role in the procedure of human body. Fuzzy logic provides an efficient and useful device for classifying drinking water quality based on limited observations. In this study, a Fuzzy Drinking Water Quality Index (FDWQI) is proposed for evaluation of water quality for drinking purpose. Fuzzy expert system makes it possible to combine the certainty levels for the acceptability of water based on an approved parameter. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>